FOUNDATION PLAYS AND ITS COMPLEXITIES IN THE INITIATION OF THE VOLLEYBALL (Fiep Bulletin - online, 2014)
In view of that he does not have theoretical referenciais that they identify and they clarify the complexities of the bedding technician has touched in the initiation of the sport voleibol, the professor must identify them to assist in the motor learning of this bedding. The present work comes to clarify some of these complexities found for beginning in the accomplishment of the bedding the technician has touched. The bedding has touched in the initiation, when analyzed theoretically it does not have you evidence of excellent complexity, but when analyzing itself how much practical the this factor of complexity increases significantly. They find many times these difficulties for receiving you vary new information at the same time, thus making it difficult the learning of the motor ability. It is necessary to have in mind that in the accomplishment of this bedding technician of voleibol, do not have only the evidences of common errors, but other aspects complex and of difficult solution, but not impossible to reach optimum performance of the same.The used methodology to identify to these complexities/difficulties was by means of questionnaires with intention to inquire the knowledge, practical of the sport and its possible difficulties the respect of the touch, together with comment of the practical one, in which 80 beginning pupils of a state school in voleibol amongst the etárias bands of 11 the 14 years.They carried through repetitive touchs, and parallel the difficulties had been written down how much to the basic positioning and other factors that intervene with the good performance of this bedding such as: force, attention, speed, agility and coordination.The study it allowed the following conclusions: (a) despite theoretically knowing the importance of the correct positioning of the body in the execution, practically the beginning ones if do not worry about (b) inadequate tonicidade (c) the same carry through the touch with the espalmadas hands (d) it has touched carried through in the height of the eyes not to the front and above of the head (e) lack of coordination in the accomplishment (f) although to have one practical weekly considerable one it presents difficulties in the bedding (g) all know the real importance of this bedding for voleibol (h) the pupils have conscience of these difficulties that they present in the execution of the touch (i) they do not execute it with attention. At last it has many complexities in this bedding that must be perceived and be worked.